1995
DOI: 10.1099/0022-1317-76-3-669
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody to the gp120-CD4 complex has differential effects on HIV-induced syncytium formation and viral infectivity

Abstract: A murine monoclonal antibody (MAb F-91-55) raised against the complex of soluble CD4 and human immunodeficiency virus type 1 (HIV-1) gpl20 had previously been found to inhibit syncytium formation without inhibiting the interaction of CD4 with gpl20, and its binding site was localized within the first two domains (D 1/D2) of CD4. We investigated whether this antibody inhibited the infectivity of HIV-1 in the CD4 + T cell lines A3.01, Sup-T1 and H9. We also examined the effect of the antibody on syncytium format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…These results confirmed that treatment of THP-1 cells with differentiating agents induced changes in cell-cell fusion that parallel changes in susceptibility to infection with the HIV-1 IIIB isolate. Consistent with our earlier report, 40 we found that significant differences existed among various uninfected cells in supporting cell-cell fusion. For example, HIV-1 IIIB -induced syncytium formation with H9 cells that tested highly positive (, 87%; MFI 5 3.1) for CD4, but expressed relatively low levels (18%; MFI 5 0.9) of CXCR4, was considerably greater than that observed with THP-1 cells expressing high CD4 and CXCR4 (Table 3).…”
Section: Hiv-1-induced Syncytium Formationsupporting
confidence: 94%
See 1 more Smart Citation
“…These results confirmed that treatment of THP-1 cells with differentiating agents induced changes in cell-cell fusion that parallel changes in susceptibility to infection with the HIV-1 IIIB isolate. Consistent with our earlier report, 40 we found that significant differences existed among various uninfected cells in supporting cell-cell fusion. For example, HIV-1 IIIB -induced syncytium formation with H9 cells that tested highly positive (, 87%; MFI 5 3.1) for CD4, but expressed relatively low levels (18%; MFI 5 0.9) of CXCR4, was considerably greater than that observed with THP-1 cells expressing high CD4 and CXCR4 (Table 3).…”
Section: Hiv-1-induced Syncytium Formationsupporting
confidence: 94%
“…39,40 After 16-20 hr of cocultivation, syncytium formation was evaluated by inverted phase-contrast microscopy at 325 magnification. Extensive cell fusion was assigned a score of 31.…”
Section: Assay For Cd4-dependent Hiv-1-induced Cell Fusionmentioning
confidence: 99%
“…Nevertheless, Mab F-91-55 inhibited both the infectivity of HIV-1 in H9 cells, and syncytium formation between these cells and chronically infected H9 cells. We proposed earlier that cellular systems used for syncytium assays differ in their susceptibility to antibodies, and that the interaction of gp120/gp41 with cell membrane CD4 may be different in cell-cell and virus-cell membrane fusion [29]. This difference may also explain our current results.…”
Section: Discussionsupporting
confidence: 54%
“…We showed previously that a monoclonal antibody to the gp120-CD4 complex (Mab F-91-55) that bound the D1/D2 domains of CD4 inhibited syncytium formation between chronically HIV-1-infected H9 cells and either A3.01 or Sup-T1 cells, even at a concentration of 0.1 µg/ml [29]. However, the antibody had a very limited effect on HIV-1 infection of A3.01 or Sup-T1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, researchers had found evidence to suggest this in previous studies. For instance Konopka, et al ., found that there was a difference in monoclonal antibody binding between cell-cell fusion and virus-cell membrane fusion with murine monoclonal antibody (MAb F-91-55) raised against the complex of CD4 and gp120 (23). In another study, additional monoclonal antibodies were found to be relatively ineffective at inhibiting cell-cell fusion as well (24).…”
mentioning
confidence: 99%